PEMATANGAN GONAD IKAN GABUS BETINA (Channa striata) MENGGUNAKAN HORMON Human Chorionic Gonadotropin DOSIS BERBEDA - Zultamin .; Muslim .; Yulisman . (Universitas Sriwijaya, 2014)
ABSTRACT The aims of this research was to study Gonad Maturity Level (GML), Index Gonado Somatik (IGS), absolute fekundity and egg diameter of Channa striata injected with the Human Chorionic Gonadotropin hormone. The research was conducted in 26th of December 2013 until 26th of January 2014 at the Fish Hatchery Unit (FHU) Batanghari Sembilan, North Indralaya District, Ogan Ilir, South Sumatra. Channa striata which as used had weights 85-105 gram per fish. The experiment was arranged in a Completely Randomized Design (CRD), (P0) No injection of HCG, (P1) 200 IU per kg fish, (P2) 250 IU per kg fish, (P3) 300 IU per kg fish. Parameters observed Gonad Maturity Level (GML), Index Gonado Somatik (IGS), absolute fekundity and egg diameter. From the four treatment experiment, P3 treatment produced the highest GML V whose the percentage was 20%, while P0 treatment did not reach GML IV and V, most of the P0 treatment (80%) only reached GML II. Based on further test of Duncan Signipicant Differences with 95% credibility level, the IGS data of Channa striata was significantly different and influential among treatments, the smallest IGS was produced from P0 treatment that is 0.43% while the largest IGS was produced from P3 treatment that is 5.91%. The smallest absolute fecundity was on the P0 treatment which was 582 eggs while the largest was on P3 treatment that is 5,775 eggs. The smallest egg diameter was on the P0 treatment which was 0.35 mm while the largest was on P3 treatment that is 0.93 mm. Hormone HCG injections of 300 IU per kg weight of the fish proved to be finalizing a Channa striata gonad. Â Keywords : Channa striata, HCG hormone, GML, IGS, egg diameter